2020
DOI: 10.3389/fimmu.2020.01258
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 and S100A9 Promote Apoptosis of Chronic Eosinophilic Leukemia Cells

Abstract: S100A8 and S100A9 function as essential factors in inflammation and also exert antitumor or tumorigenic activity depending on the type of cancer. Chronic eosinophilic leukemia (CEL) is a rare hematological malignancy having elevated levels of eosinophils and characterized by the presence of the FIP1L1-PDGFRA fusion gene. In this study, we examined the pro-apoptotic mechanisms of S100A8 and S100A9 in FIP1L1-PDGFRα+ eosinophilic cells and hypereosinophilic patient cells. S100A8 and S100A9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…BCG can stimulate TLR2/4 in bladder tumor cells to decrease cell proliferation and up-regulate apoptosis (Camargo et al, 2018). The activation of TLR4 can also induce apoptosis in multiple cancer types, such as leukemia, liver cancer, and colon cancer (Ren et al, 2018;Xiao et al, 2018;Lee et al, 2020). Cytotoxic effects and cytokine production of immune cells exert antitumor effects in the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…BCG can stimulate TLR2/4 in bladder tumor cells to decrease cell proliferation and up-regulate apoptosis (Camargo et al, 2018). The activation of TLR4 can also induce apoptosis in multiple cancer types, such as leukemia, liver cancer, and colon cancer (Ren et al, 2018;Xiao et al, 2018;Lee et al, 2020). Cytotoxic effects and cytokine production of immune cells exert antitumor effects in the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, it was shown that S100A8 and S100A9 both induce apoptosis of chronic eosinophilic leukemia (CEL) cells through impact on signaling and mRNA expression of FIP1L1-PDGFRa. Moreover, both S100A8 and A9 proteins could inhibit tumor progression of xenograft model of CEL [ 50 ].…”
Section: Pathogenic Role Of S100a8 and S100a9 In Acute Myeloid Andmentioning
confidence: 99%
“…É uma malignidade hematológica rara com níveis elevados de eosinófilos onde é caracterizada pela presença do gene de fusão FIP1L1-PDGFRA, as características diagnósticas incluem proliferação sustentada de precursores eosinofílicos com eosinofilia marcada no sangue periférico e medulo óssea (Lee et al, 2020;Morsia et al, 2020;Ruan et al, 2020).…”
Section: Leucemia Eosinofilica Crônica (Lec)unclassified